Promoting sustainable development issues through a creativity-centered e-learning course - Oskina, Anna; Darinskaia, Larisa (Nurture, 2023)
Purpose: One of the talents necessary for surviving in the modern economy is creativity which may be developed when students learn about global concerns through education for sustainable development which is recognised as having transformational power. The aim of this research is to propose an electronic course structure promoting sustainable development issues and developing students’ creativity and to test its effectiveness. Design/Methodology/Approach: During the formative pedagogical experiment (2021-2022) in the experimental group of 28 first-year television studies students, we modelled a creative seminar structure and used it to develop an electronic English language course in the Moodle Learning Management System. The control group included 27 1st year students of the same major who followed the curriculum-planned course. The results of the pre- and post-experimental questionnaire surveys were analyzed with the Mann Whitney U and ANOVA tests. Findings: According to the results of the post-experimental diagnostics, the students of the experimental group demonstrated a more positive attitude towards the e-learning environment as one conducive to the development of their creativity than the students of the control group. Conclusion: The positive shift in the experimental group students’ attitude can indicate the effectiveness of the suggested electronic course structure. Thus, it is possible to conclude that using creativity as an organizing principle in an e-learning environment allows educators to introduce the most vital worldwide challenges to students as stimuli for creative tasks and in return, receive their creative solutions.